Zonal Presidential Address - Status of virus and virus-like pathogens infecting citrus in India and future strategies for citrus improvement - AHLAWAT, Y.S. (Indian Phytopathology, 2002)
The diseases which are considered to be the main causes of decline of citrus in India, namely citrus tristeza closterovirus, citrus ringspot virus, citrus mosaic virus, citrus exocortis viroid and the greening bacterium, Liberobacter asiaticum, are briefly reviewed.